Rủi ro địa chính trị và nguy cơ mất khả năng thanh toán: Bằng chứng thực nghiệm từ các doanh nghiệp ở Đông Nam Á - Trần Phương , Thảo; Lê Anh , Tuấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper examines the effect of geopolitical risk on corporate insolvency risk in four ASEAN countries. Using an extensive sample of 13,587 firm-year observations spanning from 1995 to 2018, the authors find that geopolitical risk is positively associated with firm insolvency risk. The findings are robust to alternative estimation methods such as firm-fixed effects model, and a system-generalized method of moments regression model. Further analysis shows that the adverse impact of geopolitical risk on firm insolvency is more pronounced for manufacturing firms. However, firms with greater cash holdings can better mitigate this negative impact.
Keywords: Geopolitical risk; Insolvency risk; Cash holdings; Manufacturing firms